Historical prevalence of infectious diseases and sustainable development in 122 countries - Messono O. Omang; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2022)
This study investigates the effects of historical prevalence of infectious diseases on contemporary sustainable development. Previous studies reveal numerous proximate causes of sustainable development, but little is known about the fundamental determinants of this widespread economic concern. The novelty of this paper lies in the adoption of a historical approach that sheds light on the deep historical roots of cross-country differences in sustainable development. The central hypothesis is that historical pathogens exert persistent impacts on present-day sustainable development. Using Ordinary Least Squares (OLS) and Two Stage Least Squares (2SLS) in cross-section with data from 122 countries between 2000 and 2021, we provide support for the underlying hypothesis. Past diseases reduce sustainable development both directly and indirectly. The strongest indirect effects occur through property rights, innovation, globalization and government effectiveness. This result is robust to many sensitivity tests. Policy makers may take these findings into account and incorporate disease pathogens into the design of international sustainable development.
Keywords: B15; B40; I31; J24; Q01; 330; infectious diseases; sustainable development; economic development